Pengaruh Beban Pendinginan Terhadap Temperatur Sistem Residential Air Conditioning Hibrida Dengan Kondensor Dummy Tipe Trombone Coil Menggunakan Refrigeran Hidrokarbon - Mainil, Rahmat Iman; Thalal, Thalal; Aziz, Azridjal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
An experimental study in the hybrid air conditioning machine as air conditioner and water heater by retrofitting R-22 with hydrocarbon refrigerant (HCR-22) have been investigated. Drop-in experiments were carried out without any modification on the system. The system has been tested by varying the internal heat load 0, 1000, 2000, and 3000 W for residential cooling load simulation. The measurements taken during two hour experimental periods at 5 minutes interval times for temperature set point of 19°C. Temperature of the system is the objective of this research. The result shows refrigerant temperature of HCR-22 lower than R-22 because differences of compressor discharge pressure. Temperature discharge decrease between 16.22-24.02 ˚C. For conditioned room, room temperature in every internal heat load was relative same. And water temperature in 50 L storage are 46.58-48.81 ˚C.Keywords : Hybrid Air Conditioning, Dummy Condenser, Hydrocarbon Refrigerant HCR-22, Cooling Load.